THE INFLUENCE OF CUSTOMER PERCEPTION AND CUTOMER ATTITUDE ON CUSTOMER PURCHASE INTEN-TION OF ZALORA ONLINE SHOP IN MANADO - Tangkere, Imanuela Hana (Sam Ratulangi University, 2016)
The user of the internet has been increasing significantly from year to year. The Internet is, not only, used to find information and communication, but the internet is also used for browsing like fashion products. Many people prefer online goods because of its simplicity, saving time and comfort. The development of E-Commerce in Indonesia at this time is very fast. There are many online shops that can be an option for us in buying and selling goods.The online shop is a medium that allows the customer to purchase goods or services directly from sellers with media on the internet using a web browser.Â Nowadays, many online shops are competing to attract the attention of customers. Zalora is one of the online shop site which is very sought by most of the people in Indonesia, especially in Manado city because Zalora sells fashion products for men and women. Zalora Online Shop sells many variants of products from various brands.This research is aimed to analyze simultaneously and partially influence of customer perception and customer attitude on customer purchase intention of Zalora online shop . Theories supporting research are customer perception, customer attitude and customer purchase intention. The population refers to Zalora customers in Manado city with sample size as many as 150 respondents. The sample will be Random Sampling, in order to get results quickly and efficiently obtain the information needed in this research. This research used quantitative analysis by using questionnaires and used Ordinal Regression Analysis. Result and conclusion show customer perception and customer attitude have significant and positive influence on customer purchase intention. Finally, future research should add more variable or interviewing to make a better result for the influence on purchase intention.